Nothing but trouble eaudiobook Kevin kerney mysteries series, book 10. - McGarrity, Michael (Kevin Kerney, 2006)
Former deputy sheriff Michael McGarrity's stunning cop mysteries, including Slow Kill, have been nominated for the coveted Anthony Award. The New York Timessays, "McGarrity has a cunning mind for crime fiction." When pro rodeo star Johnny Jordan returns to Santa Fe, he asks his childhood friend, police chief Kevin Kerney, to serve as a consultant on a new film being staged along the Mexican border. Seeing an opportunity to get paid while enjoying a long-overdue vacation, Kerney agrees, and brings along his wife, Lieutenant Colonel Sara Brannon, and their young son, Patrick. But on the road to the isolated location, they find the dead body of an undercover federal agent—so much for relaxation. Filled with unbridled suspense and accurate depictions of police procedures, Nothing but Trouble benefits from the perspective of a "man who has been there and done that," according to New York Times bestselling author Tony Hillerman. "The series remains one of crime fiction's most readable."—Kirkus Reviews